A new species of Neckera (Neckeraceae, Bryophyta) from northern Vietnam - Enroth, Johannes; Touw, Andries (Phytotaxa, 2015)
Neckera praetermissa Enroth & Touw spec. nov. (Neckeraceae) is described from northern Vietnam. It is morphologically closest to the SE Asian N. undulatifolia (Tix.) Enroth, with which it shares the similar, ovate-ligulate and symmetric leaves with coarsely dentate apices, and strongly incrassate and porose leaf cell walls. However, N. undulatifolia has the stems up to 10 cm long and a distinct costa reaching to 5/6 of leaf length, while the stems of N. praetermissa are to c. 3 cm long and the leaves are ecostate or with a weak costa reaching to 1/6 of leaf length at most.